PENERAPAN MODEL BANK SAMPAH DALAM MENINGKATKAN KEBERSIHAN LINGKUNGAN - Lilis Karwati (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2021)
The purpose of the study is to describe the application of the waste bank model in improving environmental hygiene. The implementation of the waste bank model has several stages of activities, namely 1) Socialization of the first phase, 2) The establishment of waste bank management team, 3) Waste savings training, 4) Socialization of the second phase, 5) Garbage saving servants consisting of household waste sorting, depositing, weighing, recording, garbage transportation, storage and money collection as well as waste recycling activities, and 6) Evaluation. The method used in the study is descriptive method with qualitative approach. Data collection techniques through observation, interview and documentation. Data analysis techniques used are data reduction, data presentation and conclusion drawing. The results of the study found that after the existence of waste banks with the implementation of activities through a 5p approach (possibility, strengthening, protection, disposing and maintenance) now the community manages waste by collecting, sorting and managing waste through waste savings and waste recycling that makes the environment cleaner and neatly organized. In addition, the existence of waste banks also has a positive impact on society that can be seen from the health, education and socioeconomic aspects